EFISIENSI USAHATANI TEBU DI KABUPATEN PURWOREJO - Dewi Intan Febianti; Jamhari Jamhari; Slamet Hartono (Agro Ekonomi, 2015)
Sugar is one of the most crusial comodity that the demand continue to increase along with population growth. Nowdays, Indonesia s sugar production can not be able to meet the demand Optimal allocation offactors production can deliver optimum production of sugarcane with the appropriate combination of its resources. This study was undertaken toidentify the factors affecting sugarcane production in Purworejo, to identify allocative efficiency of sugarcane farming, to identify the revenue and profit of sugarcane farming and to identify thefactors affecting revenue of sugarcane s farmers in Purworejo. Data were analyzed using descriptive statistics. The location of the study has been chosen in Purworejo, MiddleJava. Data were collected from 60 sugarcane farmers. The result showed that factors affecting sugarcane production in Purworejo were land use, seeds, phonska, pesticide, onfarm labour and harvest labour. Allocative efficiency was examined by Ki function, Ki showed> 1. It means that all significant major inputs were not optimum. The allocative efficiency couldbe achieved by increasing of existing production inputs. Net revenue was Rp. 19.824.598,85 per hectare and the profit per hectare was Rp. 16.785.428,07. Sugarcane farming RIC ratio in Purworejo was 2,19 (RIC> 1). It showed that is suitable to be extend The analysis revelaed that factors affecting revenue of sugarcane farming were land use, normalized seeds price,normalized phonska price and normalized labour price.